Design of Noble Metal Electrocatalysts on an Atomic Level. Issue 2 (31st October 2018) - Chao, Tingting; Hu, Yanmin; Hong, Xun; Li, Yadong
Abstract: Nanostructured noble metal‐based materials have been considered in recent years as promising catalysts for energy storage and conversion. One of their prominent applications is a series of electrochemical processes in fuel cells, as they show excellent electrocatalytic performance towards the reactions occurring at both anode and cathode. Nowadays, considerable efforts have been devoted to boosting the catalytic activity and minimizing the used amount of precious metals. In this review, we introduce the recent advances regarding controllable synthesis of noble metal electrocatalysts at an atomic level. Important electrochemical reactions, such as oxygen reduction reaction (ORR), hydrogen evolution reaction (HER), oxygen evolution reaction (OER), electroreduction of carbon dioxide (CO2 ) and so on, catalyzed by precisely controllable noble metal electrocatalysts will be highlighted. This review primarily focuses on the exploration for the relationship between atomic‐level structure of electrocatalysts and their enhanced catalytic property combining theoretical calculations and experiments. Finally, perspectives for further advances of noble metal nanomaterials are proposed to realize rational design of electrocatalysts at an atomic level. Abstract : Noble art of materials design : noble metal based electrocatalysts show promising performance in energy storage and conversion applications. This review summarises recent advances in the rational design on the atomic level of noble metal‐based materials for applications in electrocatalysis.